Simulation Analysis and Experimental Verification of High-Speed Impact of Rocky Asteroids - Fan Huang; Zhiqing Geng; Binqiang Luo; Yuming Peng; Liang Xu; Wei Wang; Biyue Pan; Dongyu Li (Sensors)
Kinetic impact is an effective way to deal with threatening asteroids, and the momentum transfer coefficient during the impact process is an effective indicator for evaluating the impact effect. This article is based on the use of the Smoothed Particle Hydrodynamics (SPH) method to establish a simulation model of high-speed impact of flying discs on granite targets, and obtain parameters such as the shape of the splashing material and the distribution of the target damage during the impact process. An analysis was conducted on the influence of different impact velocities on the kinetic energy transfer coefficient, and it was found that the momentum transfer coefficient increased with the increase in impact velocity, from 1.59 at 5 km/s to 1.96 at 11.7 km/s. A ground high-speed impact system with a speed of over 10 km/s has been established, and the actual momentum transfer coefficient has increased from 1.73 at 7 km/s to around 2.06 at 11.7 km/s. The variation trend of kinetic energy transfer coefficients obtained from experiments and simulations is consistent, with an error of basically within 10%, and the simulation results are effective. The simulation and experimental analysis of high-speed kinetic impact can provide a reference for the engineering implementation of asteroid impact defense missions.